2011
DOI: 10.1021/ie1017089
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of CuO Nanoparticles: Study on Effects of Operational Conditions on Yield, Purity, and Size of the Nanoparticles

Abstract: Hydrothermal synthesis of CuO nanoparticles under near-critical and supercritical conditions was investigated from two different standpoints in the current study. The first standpoint was optimization of “yield”, “purity”, and “size of the nanoparticles” that were optimized at T = 500 °C, time = 2 h, [Cu(NO3)2] = 0.1 mol dm−3, and pH 3. This was achieved by undertaking an orthogonal experiment design methodology and performing different instrumental analyses, such as X-ray diffractometry, inductively coupled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Therefore, one can conclude that the metal nitrate salts are good candidates to be used as precursors. On the other hand, our findings indicated that the formation of some nitrate, hydroxide, or hydoxinitrates complexes as the byproducts of metal oxide formation reaction is unavoidable [16,29]. The existence of such…”
Section: Introductionmentioning
confidence: 59%
“…Therefore, one can conclude that the metal nitrate salts are good candidates to be used as precursors. On the other hand, our findings indicated that the formation of some nitrate, hydroxide, or hydoxinitrates complexes as the byproducts of metal oxide formation reaction is unavoidable [16,29]. The existence of such…”
Section: Introductionmentioning
confidence: 59%
“…There are several synthesis routes such as solution based technique [15], hydrothermal [16], microwave [17] and ultrasonics [18] have been developed to prepare well-defined nanostructures with different morphologies. The size, shape and morphology of the CuO nanostructures are greatly affected by various parameters such as concentration of constituents, temperature and aging time [15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some recently reported methods for preparing CuO nanoparticles include the hydrothermal method [3,11], the precipitation method [4,5,7,8], the sol-gel method [12], the flame spray pyrolysis method [13], and solution combustion method [9]. Of these schemes, the precipitation method is particularly simple, and has attracted considerable interest from industry owing to its low required energy and temperature, and cost-effectiveness in large-scale production with high yield [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%